2020
DOI: 10.1111/1751-2980.12935
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19: A strong call for remote medicine in inflammatory bowel disease

Abstract: Coronavirus disease 2019 (COVID-19) is a disease caused by the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which was first reported in Wuhan (Hubei Province, China) after a series of patients with acute respiratory disease were diagnosed in December 2019. 1 Due to the rapid spread of the virus across

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Within the IBD subspecialty, data on synchronous telecare is lacking but mHealth apps have a strong presence and have shown to be helpful for establishing lines of communication between patients and their clinicians 6,12 . IBD patients have shown positive attitudes towards receiving ongoing digital care for follow‐up consultations 17‐21 . IBD patients have also significantly benefited from telecare by having reduced travel time, distances and out‐of‐pocket costs when accessing follow‐up appointments virtually instead of in‐person 3 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the IBD subspecialty, data on synchronous telecare is lacking but mHealth apps have a strong presence and have shown to be helpful for establishing lines of communication between patients and their clinicians 6,12 . IBD patients have shown positive attitudes towards receiving ongoing digital care for follow‐up consultations 17‐21 . IBD patients have also significantly benefited from telecare by having reduced travel time, distances and out‐of‐pocket costs when accessing follow‐up appointments virtually instead of in‐person 3 .…”
Section: Discussionmentioning
confidence: 99%
“…16 Similarly, from Egypt, Khorshid et al reported that 78% of their IBD patients requested that remote medicine continued beyond the pandemic. 17 An Australian retrospective qualitative analysis found that 88.1% of their patients were either 'satisfied' or 'very satisfied' with the transition to telecare at a tertiary IBD centre. 18 there was no significant difference in baseline characteristics between patients who accepted and patients who rejected telecare.…”
Section: Infl Ammatory Bowel D Is E a S Ementioning
confidence: 99%
See 1 more Smart Citation